Penggunaan Cooperative Learning Model Jigsaw dalam Peningkatan Aktifitas Siswa pada Pembelajaran PKn di SMPN 1 Kota Pariaman - Yulfianti Yulfianti (Journal of Education on Social Science (JESS), 2017)
This study aimed to increase the student learning activity in Citizenship Education at classroom VIII.5 SMP Negeri 1 of Pariaman City in the 1st half semester of 2015/2016. This study was conducted through Classroom Action Research with the application of the Jigsaw model in cooperative learning. This study was conducted in two cycles. The finding of this study showed that the use of Jigsaw model in Citizenship Education classroom could increase the activity of the learners, the average value of their learning outcomes, and learning completeness of the learners. The conclusion of this study was that there were increased activities in the student learning in Citizenship Education by using the Cooperative Learning of Jigsaw model so as to improve learning outcomes of the students in grade VIII.5 SMP Negeri 1 of Pariaman City.